Tindakan Invasif sebagai Pilihan Tatalaksana pada Kasus Trombosis Vena Dalam - Kemala, Yuke Fawziah; Kurnianingsih, Novi (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Deep Vein Thrombosis (DVT) refers to thrombus formation in the deep vein, usually legs, which causes inflammation, and potentially causing disruption of blood flow. Anatomically, DVT is classified as upper and lower extremity DVT. A study in the USA reported 375,000–425,000 new cases of VTE diagnosed per year, of which 50/100,000 cases were DVT. Pathophysiology of DVT is closely related to the Triad of Virchow, i.e. hypercoagulability, stasis and endothelial injury. Establishing DVT diagnosis comprises finding clinical presentation or calculating probability pre-test score, obtaining laboratory examinations, such as D-dimer and imaging test. Venous ultrasound is the gold standard for highly-suspected DVT, while the others are Computed Tomography Venography (CTV) and Magnetic Resonance Venography (MRV). The aim of DVT management based on onset, because immediate treatment in the acute phase, known to reduce significantly the incidence of recurrence, pulmonary embolism and major bleeding. DVT treatment can be divided into non-invasive (i.e. anticoagulation and stocking compression) and invasive. If there are no thrombolysis contraindications, endovascular techniques, such as CDT; PMT; PCDT; venous stenting; as well as IVC/SVC filter placement are recommended. Meanwhile, surgical techniques (i.e. surgical thrombectomy; surgical decompression and vein bypass) are an option if conservative management is unsuccessful, high-risked of life-threatening pulmonary embolism with a low-risk of bleeding, or has severe PTS. By knowing the diagnostic techniques and indications of invasive treatments, it is prospected to plan the appropriate management for each patient, so that increases the successful rate as well as reduce intrahospital and long-term complications.